ANALISIS SEMANGAT KERJA KARYAWAN (STUDI PADA INDUSTRI COLD STORAGE DI KOTA JUWANA) - Wahyu Ika Pramono; Rauly Sijabat; Bayu Kurniawan (International Forum of Researchers and Lecturers, 2023)
This study aims to determine the effect of Workload, Work Communication, Work Environment, on Employee Morale in the Cold Storage Industry in Juwana City. This study used a nonprobability sampling research method with a purposive sampling method. The population used in this study were all employees working in the Cold Storage Industry in Juwana City and the sample used was 110 employees. This study uses a nonprobability sampling research method with a purposive sampling method (saturated sampling). Data analysis in this study used the technique of Multiple Linear Regression Analysis with the statistical package for the social sciences (SPSS) program. The results of the analysis and discussion show that the variables Workload, Work Communication, Work Environment, have a direct effect on Employee Morale. The Variable of Work Communication partially has no positive and significant effect on Employee Morale. Variables Workload, Work Communication, work environment simultaneously have a positive and significant effect on Employee Morale in the Cold Storage Industry in Juwana City.